Ritual Pengobatan Beliatn Sentiyu Sebagai Ide Penciptaan Tari Video “Manusia Beliatn” - Muhammad Adiyad (Joged, 2023)
RINGKASAN“Manusia Beliatn” sebuah karya video tari yang terinspirasi dari gerak Bepusing (berputar) dalam ritual pengobatan beliatn sentiyu suku Dayak Benuaq. Tema dari karya ini adalah Doa sebagai ungkapan permohonan manusia kepada Tuhan agar manusia yang terkena sakit bisa disembuhkan. Pemilihan ritual pengobatan beliatn sentiyu sebagai sumber inspirasi bermula dari pengalaman empiris penulis ketika melihat ritual beliatn sentiyu. Suara musik dan gerakan berputar menginspirasi untuk mengeksplorasi gerak dan simbol dalam upacara ini. “Manusia Beliatn” merupakan karya tari yang bersifat alih wahana digital dengan metode sinematografi, yang terletak pada teknik pengambilan gambarnya.ABSTRACT"Manusia Beliatn" is a dance video work inspired by bepusing (spinning) movements in the beliatn sentiyu ritual of the dayak benuaq tribe which is studied through choreographic aspects. The theme of this work is Prayer as an expression of man to God so that people affected by illness can be healed. The selection of beliatn sentiyu treatment rituals became a source of inspiration starting from the aesthetic experience of the proximity of space and sound in the course of life the author heard the beliatn sentiyu ritual and the sound of music as well as rotating movements caused a sense of wanting to explore in motion and the meaning of value in an aesthetic reception. "Manusia Beliatn" is a dance work that is transferred to digital vehicles by the method of cinematography, cinematography with the relationship of the work "Manusia Beliatn" lies in the technique of taking it.